Hissss! - Inkpen, Mick (San Diego : Harcourt, 1999)
On a hot summer day when Kipper the dog discovers a leak in his wading pool, he fixes it in a very unusual way.
"Red wagon books."
"Ages 2-5"--cover p. [4].
Keywords: Dogs -- Fiction; Summer -- Fiction